2021
DOI: 10.1186/s12955-021-01785-x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal tobacco exposure and health-related quality of life during pregnancy: a national-based study of pregnant women in China

Abstract: Background With the increase of the number of smokers, tobacco exposure among pregnant women is becoming more and more common. Pregnant women exposed to first-hand smoke and second-hand smoke are susceptible to physiological and psychological health issues has been proved in previous studies. Nevertheless, there are no enough studies focus on the impact of third-hand smoke during pregnancy. This study aimed to assess and compare health-related quality of life for pregnant women with exposure to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Third, several potential risk factors for HDP, including a family history of hypertension, maternal smoking habit, physical activity, and status of maternal nutrition during pregnancy, were not collected in our study. While for maternal smoking habit, previous studies reported a very low prevalence (0.6%–3.8%) among pregnant women in China, and about 82.9% of smoking women quit smoking after they were pregnant. , Therefore, the confounding effect of maternal smoking habit might be toward null. Last, limited by exposure assessment techniques, only six major components of PM 2.5 were investigated in relation to the risk of HDP, and many other toxicity components (i.e., heavy metals) were not studied.…”
Section: Discussionmentioning
confidence: 99%
“…Third, several potential risk factors for HDP, including a family history of hypertension, maternal smoking habit, physical activity, and status of maternal nutrition during pregnancy, were not collected in our study. While for maternal smoking habit, previous studies reported a very low prevalence (0.6%–3.8%) among pregnant women in China, and about 82.9% of smoking women quit smoking after they were pregnant. , Therefore, the confounding effect of maternal smoking habit might be toward null. Last, limited by exposure assessment techniques, only six major components of PM 2.5 were investigated in relation to the risk of HDP, and many other toxicity components (i.e., heavy metals) were not studied.…”
Section: Discussionmentioning
confidence: 99%
“…China has the highest tobacco production and the most tobacco consumers in the world, and approximately 47.2% of Chinese males had smoking habits in an investigation conducted in 2013 [2]. Thus, with an increasing number of smokers, many nonsmoking people, especially pregnant women, children and elderly individuals, are more likely to suffer from passive tobacco exposure (so-called secondhand smoke (SHS)) [3,4]. Over the past few decades, many epidemiological studies have also suggested that the exposure of pregnant women to SHS by their partners was very common during pregnancy, even though they were nonsmokers [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, some investigations indicated that the self-reported rate of SHS exposure was relatively high in the third trimester [8][9][10]. Previous studies have shown that exposure to SHS is more serious than active smoking [3,11,12] because it is 3 to 4 times more damaging per gram of particulate matter than smoke directly inhaled by a smoker [13]. An increasing number of studies have indicated that exposure to SHS affects almost every type of adverse pregnancy outcome, such as depression disorders, low levels of health-related quality of life, preterm labor, rupture of membranes, and fetal weight loss [3,14,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…QoL not only depends on the time course of pregnancy but can be detrimentally affected by factors such as nausea, sleep difficulties, environment factors (i.e., tobacco exposure/intake) [7], financial challenges, lumbopelvic pain [8], or domestic violence [6]. Additionally, changes in body mass index, weight gain (specifically, excessive gains), or other complications can negatively influence one's self-perception of health status [9].…”
Section: Introductionmentioning
confidence: 99%